Pharmaceutical supply chain transformation through application of the Lean principle: A literature review - Berty Argiyantari; Togar M. Simatupang; Mursyid Hasan Basri (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: This study aims to review the previous literature on the topic contained in the title in order to identify gaps in the existing research relating to lean supply chain-related issues within the pharmaceutical industry since limited attention has been devoted to this sector. Design/methodology/approach: This study presents a systematic literature review that proposes an analysis and classification of the previous literature as falling within one of four categories, namely; the supply chain area, research approach, research objective, and lean supply chain elements. Findings: The results of this study indicate that most attention was focused on manufacturing, while upstream suppliers, downstream activities and the entire supply chain process have received comparatively scant consideration. Similarly, the issues of information technology management, supplier management, customer relations, and logistics management as well as practitioner involvement represent inadequately developed topics. Future research should address these omissions, in addition to the integration of quality compliance and digital innovation as they relate to pharma 4.0. Practical implications: This article serves as a guide to acquiring sufficient knowledge of the pharmaceutical supply chain prior to implementing lean supply chain management. Moreover, it is anticipated that the research it contains will contribute to eradicating the knowledge gap by expanding the existing limited body of literature on the adoption of lean approach in the PSC. Originality/value: This study is one of a limited number of literature analyses potentially helpful in developing a roadmap of lean principle application to the pharmaceutical supply chain.
Keywords: 650; lean principle; pharmaceutical; supply chain; literature review; lean supply chain